The Mawdu‘i Method in Hadith Studies: Conceptual Framework and Practical Application - Zainuddin, Zainuddin (El-Sunan: Journal of Hadith and Religious Studies, 2025)
The thematic (mawḍū‘ī) approach to hadith is a methodological framework that focuses on collecting, classifying, and analyzing prophetic traditions (ḥadīth) related to a specific theme in order to achieve a comprehensive and applicable understanding. This study employs a qualitative library research method, drawing upon primary sources such as canonical hadith collections and secondary literature in the field of ʿUlūm al-Ḥadīth. The findings indicate that the thematic hadith methodology proceeds through several systematic stages: determining the research theme, exploring key concepts and vocabulary, gathering relevant hadith through takhrīj procedures, verifying the authenticity of isnād and matn, and analyzing the content of the traditions by considering asbāb al-wurūd, linguistic dimensions, and their correlation with Qur’anic verses. Furthermore, this study highlights three major interpretive techniques in thematic hadith research: (1) textual interpretation, which emphasizes the literal meaning of the hadith as expressed in its wording; (2) intertextual interpretation, which relates hadith to other narrations or Qur’anic verses with similar meanings; and (3) contextual interpretation, which emphasizes the relevance of hadith to socio-historical realities and considerations of public benefit (maṣlaḥah). A comparative analysis of these techniques reveals that each possesses its own strengths and limitations but are methodologically complementary: textual interpretation safeguards the linguistic authenticity of hadith, intertextual interpretation ensures the coherence of Islamic teachings, and contextual interpretation strengthens the relevance of hadith in addressing contemporary issues. Therefore, integrating these approaches is essential in thematic hadith methodology to produce interpretations that are not partial but comprehensive, normative, and applicable. The study concludes that the mawḍū‘ī method holds significant epistemological value in advancing contemporary hadith studies across legal, ethical, educational, and socio-cultural domains.